Prthas inmunization digest - Parthasarathy, A. (Jaypee Brothers Medical Publishers, 2011)
An updated and revised book with detailed information on various aspects of immunization. Practical guidelines are incorporated on Vaccine Administration and Safe Injection Practices. Diagrams' showing administering multiple vaccines at the same sitting provides a visual guide.